Role of Sesamoid Position and Recurrence of Hallux Valgus Deformity - Thomas L. Lewis BSc (Hons) MBChB (Hons) FRCS (TrMFSTEdOrth); Robbie Ray MBChB, ChM(TFRCSed(TrO) FEBOTOrth); Evelyn Murphy MBBCh BAO MCh FRCS (TrOrth); Min Jia Chua MB BS FRCSEd; Clare Watt BNurs; Peter Robinson BSc(Hons), MBChB, FRCS(TrOrth); Peter Lam MBBS (Hons), FRACS, FAOA (Foot & Ankle Orthopaedics)
Category: Bunion; Midfoot/Forefoot Introduction/Purpose: One of the most important complications of hallux valgus surgery (when performed either through an open or minimally invasive technique) is recurrence of deformity. Recurrence is often multifactorial due to patient factors such as anatomy, pre-operative deformity, soft tissues, comorbidities and compliance with instructions and surgical factors such as choice of surgical technique, implant and technical competency. The aim of this study was to investigate the role of sesamoid position and impact on recurrence of hallux valgus deformity following percutaneous minimally invasive hallux valgus surgery. Methods: A prospectively maintained research registry of fourth-generation percutaneous metatarsal extra-capsular transverse osteotomy (META) for hallux valgus between 2017-2023 was retrospectively analysed to identify feet that had recurrence of hallux valgus deformity (defined as HVA>20°). Comparative analysis was then performed to assess the impact of pre-operative deformity and sesamoid position on recurrence. Radiographic deformity and sesamoid position (including ‘Round sign’) were assessed according to AOFAS guidelines. Secondary outcomes included clinical patient reported outcome measures including the Manchester-Oxford Foot Questionnaire (MOXFQ) and Visual Analogue Scale for Pain. All p-values < 0.05 were considered significant. Results: Between November 2017 and January 2023, 729 feet underwent META with minimum 12-month radiographic follow up (mean 2.6±1.3 years). There were 33 cases with HVA>20° at final radiographic follow up (4.5%). There was a statistically significant difference in sesamoid position between feet which had recurrence with higher rates of Grade 2 and 3 compared to those which didn’t (p < 0.05). There was no significant difference in Round sign assessment between cases which recurred and those that did not (p=0.27). The mean pre-operative deformity in cases which underwent recurrence was significantly greater than those which did not recur (p < 0.05), (HVA:44.3±6.5, IMA:15.6±3.7° compared to HVA:28.8±8.0°, IMA:12.8±3.3°). Of the 33 cases which had recurrence, 13 demonstrated HVA>20° at 6 month XR suggesting incomplete deformity reduction. Conclusion: Incomplete reduction of sesamoids appears to be a risk factor for recurrence. Incomplete deformity reduction at the time of surgery, particularly in cases of severe deformity (HVA>40°) is an important factor to acknowledge when considering risk of recurrence. The deformity correction achieved through bony correction (using the fourth-generation META technique) appears to be maintained from 6-months to final radiographic follow up suggesting that recurrence is predominantly linked to incomplete deformity reduction and sesamoid position at the time of surgery.